Fast-tracking maize varietal replacement in Ethiopia. - CGIAR Research Program on Maize (2018)
The replacement of older, climate-vulnerable maize varieties with improved climate-resilient hybrids into stress-prone maize farming systems has contributed to improved productivity and food subsistence in Ethiopia. MAIZE has been instrumental in fast-tracking maize varietal replacement in Ethiopia through successful engagement with public- and private-sector institutions. MAIZE’s successful development and commercialization of improved maize varieties, in particular variety BH661, through projects like NuME, DTMA and WEMA, offers a valuable model for breeders, seed companies, extension agents, regulatory and policy makers.